Evaluation of final quality of germinated brown rice following steaming and hot-air drying at different temperatures - Langkapin, Jaturong; Parnsakhorn, Sunan; Oupathumpanont, Orawan; Samseemoung, Grianggai (Agriculture and Natural Resources, 2023)
Importance of the work: Heat treatment factors (steaming and different drying temperatures) can influence the final quality of germinated brown rice. Objectives: To evaluate the final quality of germinated brown rice (GBR) under steaming and hot air drying at different temperatures. Materials & Methods: Brown rice was soaked at 40°C for 4 hr before being incubated at 40°C and 90% relative humidity for another 20 hr to make the GBR samples. Then, the GBR was separated into two groups that were subjected to different treatments: steamed drying (S) and non-steamed drying (NSD). The S group consisted of GBR samples that were steamed at 100°C for 10 min before being individually dried at temperatures of 20°C, 40°C, 80°C or 160°C, whereas the NSD GBR samples were dried at these same temperatures without pre-steaming. Results: Germination increased the plate count of microorganisms to 5.67×106 colony forming units (CFU)/g; however; this was reduced during high-temperature drying (2.57×103 CFU/g). The yellowness of the NSD increased with increasing drying temperature (from 23.65 to 25.21); however, there was no impact of the yellowness for the S group. The lowest lightness (L*) of the S group was obtained by drying at low temperatures (20°C, 40°C), with significant increases to 58% and 60% after drying at 80°C and 160°C, respectively. It also increased the pasting properties of the NSD and S treatments. Scanning electron microscopy confirmed the gelatinization of the S group at all drying temperatures. Main finding: GBR was improved through steaming and subsequent drying which also removed moisture from the grain mass to enhance longer-term storage microbial quality.